Optimizing Microbial Composition in Soil Macroaggregates Enhances Nitrogen Supply Through Long-Term Straw Return - Lei Xu; Ganghua Li (Agronomy)
Soil nitrogen (N) is critical for crop yield. Although previous studies have shown that straw return enhances soil mineral N availability, the response of soil aggregate microbes to straw return and its impact on soil mineral N availability remains unclear. We conducted a 13-year experiment to explore how soil N mineralization potential, fungi, and bacteria within soil aggregates responded to straw return. Our findings indicated that straw return significantly increased mineral N concentrations in soil macroaggregates, with no statistically significant effect observed on microaggregate composition. We observed increased microbial community α-diversity, enhanced co-occurrence network stability, and an increase in functional groups associated with N (nitrate respiration, denitrification, nitrite denitrification) and carbon (saprotrophs, saprotroph–symbiotrophs, patho-saprotrophs) cycling within the aggregates. Additionally, microorganisms in macroaggregates were influenced by total N, while those in microaggregates were affected by soil total organic carbon and C–N ratio. A sensitivity network analysis identified specific microorganisms responding to straw return. Within macroaggregates, microbial community shifts explained 42.88% of mineral N variation, with bacterial and fungal β-diversity contributing 27.82% and 12.58%, respectively. Moreover, straw return upregulated N-cycling genes (N ammonification: sub, ureC, and chiA; nitrification: amoA-AOB; denitrification: nirK, nirS, nosZ, norB, and narG; and N fixation: nifH) in macroaggregates. Partial least squares path modeling revealed that N availability in macroaggregates was mainly driven by ammonification, with bacterial β-diversity explaining 23.22% and fungal β-diversity 15.16% of the variation. Our study reveals that macroaggregates, which play a crucial role in soil N supply, are highly sensitive to tillage practices. This finding provides a practical approach to reducing reliance on synthetic N fertilizers by promoting microbial-mediated N cycling, while sustaining high crop yields in intensive agricultural systems.